(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Aim Of This Research Is To Determine The Degree Of Availability Of Educational Design Skills According To The Standards Entrance Among Students Of The College Of Education, Specialist (Curricula And Class Teacher) At Tishreen University, And The Impact Of Variables (School Stage, Gender, Specialization) In That, And In Order To Achieve The Objectives Of The Research, The Descriptive Approach Was Used From During The Design Of A Questionnaire That Consisted Of (34) Phrases Distributed Over Four Dimensions, And The Research Sample Consisted Of (185) Male And Female Students In The College Of Education, From A Specialist (Curricula, Class Teacher), And The Most Prominent Results Of The Research Were: The Degree Of Availability Of My Skills (Formulation Of Educational Standards, Planning Lessons According To The Standards Entrance) Was Achieved By The Students Of The Faculty Of Education (Curriculum Specialist And Class Teacher) At Tishreen University At An Intermediate Level. The Degree Of Availability Of My Skills (Curriculum Evaluation According To The Standards Approach, Curriculum Development According To The Standards Entrance) Among Students Of The Faculty Of Education (Curriculum Specialist And Class Teacher) At Tishreen University Was Low. - There Are Statistically Significant Differences In The Degree Of Availability Of Educational Design Skills According To The Standards Entrance Among Students Of The College Of Education, Specialist (Curricula And Class Teacher) At Tishreen University, According To The Variable Of The Academic Stage In Favor Of Graduate Students, And According To The Variable Of Specialization In Favor Of Students From The Specialization (Curricula). - There Are No Statistically Significant Differences In The Degree Of Availability Of Instructional Design Skills According To The Standards Approach Among Students Of The Faculty Of Education At Tishreen University According To The Gender Variable.